2016
DOI: 10.1007/s11356-016-7312-y
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidative processes and membrane separation for micropollutant removal from biotreated domestic wastewater

Abstract: The presence of micropollutants in sewage is already widely known, as well as the effects caused by natural and synthetic hormones. Thus, it is necessary to apply treatments to remove them from water systems, such as advanced oxidation processes (AOPs) and membrane separation processes, which can oxidize and remove high concentrations of organic compounds. This work investigated the removal of 17β-estradiol (E2), 17α-ethinylestradiol (EE2), and estriol (E3) from biotreated sewage. Reverse osmosis processes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Silva et al [73] ) eliminated the presence of the two first estrogens and 91% of estriol. The authors concluded that AOP was effective although the membrane process, which couldn't remove estrogens tested.…”
Section: Advanced Oxidation Processmentioning
confidence: 99%
“…Silva et al [73] ) eliminated the presence of the two first estrogens and 91% of estriol. The authors concluded that AOP was effective although the membrane process, which couldn't remove estrogens tested.…”
Section: Advanced Oxidation Processmentioning
confidence: 99%
“…The two significant limitations observed from this study were a decline in the filtration capacity, due to fouling and quick fouling in the MF membrane; thus, reducing the removal efficiency from 37% to 24%. Interestingly, a higher removal efficiency of 97% was reported by Al-Rifai et al [ 58 ] as MF and RO were combined in treating EDCs. However, BPA of a concentration of 500 ng/L was discovered in the effluent after the treatment process, and higher energy demand was required.…”
Section: Rejection Of Edcs By Membranesmentioning
confidence: 93%
“…Globally, several EDCs contaminants have been detected in effluent discharged from WWTF, frequently at a proportion of hundreds of nanograms per liter to micrograms-per-liter scale [ 40 ]. Furthermore, there has been an increasing amount of literature that emphasized and reported series of health challenges associated with endocrine-disrupting compounds, such as interference with the endocrine system of man and animals by influencing the synthesis, release, transport, metabolism, and excretion of hormones in the body, mimicking, blocking, disrupting the normal function of hormone system in humans thereby causing severe effects, such as abnormal reproductive growth, cardiovascular changes, reduction of sperm reproduction in humans which result to low fertility, thyroid and adrenal gland dysfunctions, immune, neurological diseases, developmental dysfunctions throughout the fetal period, stimulation of breast cancer in women, development of testicular and prostate cancer, a decline in reproductive fitness of men and increased threat to human [ 19 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. In addition, EDCs have also be linked with altered behavior and obesity in children, reduced gonadal development and viability, alter physiological status in humans and wildlife [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, exposure to EDCs by humans and wildlife results from the intake of chemicals through foods and drinking water consumption, which results in biomagnification and bioaccumulation, particularly in species at the highest level of the food web [ 44 ]. Furthermore, research findings have also reported negative impacts of EDCs on animals, as they affect the hormonal systems of organisms, binding to receptors in animals and mimicking the activities of estrogen, obstructing the normal action of the endocrine system and inciting reproductive syndrome, feminization, and carcinogenesis in numerous wildlife animals; they affect the synthesis release, transport, and interface with female estrogen and disrupt the reproductive growth and behavior of animals; and they interfere with the delicate balance of the endocrine system of animals, altering the physical status in wildlife and natural hormone activities and threatening the reproductive biology and health of an animal populace [ 42 , 43 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%